A BREAKTHROUGH SYLLABUS IN TEACHING LANGUAGE TESTING COURSE - Tedi Rohadi (IAIN Syekh Nurjati Cirebon, 2017)
Abstract: The word â€œtesting or assessmentâ€ has always been a scarry thing for anybody especially students. This perception is worsened by the fact that time allotment of the course is limited and the scope of materials to be covered is overloaded. As a result, the students are overwhelmed, confused, and even frustrated. The paper is a report of a breakthrough syllabus in teaching language testing course resulted from a classroom action research in effectively transforming such frightening, bewildering, and discouraging nuances to be a conducive teaching-learning circumstance. Theories and concepts underpinning the study as well as research methodology will initiate the paper. The next part of the paper will discuss the so called â€œa breakthrough syllabusâ€ itself as the focus of the study and its implementation and findings. The paper will not only elaborate some problems that were encountered during the implementation but also will provide some suggestions to anticipate those potential problems in the end part of the paper. The discussion last but not least enlighten every aspect involved in the study. Â Keywords: Assessment, Syllabus, Language Testing